Behavioral And Fertility Factors Associated with Acceptance or Non-Acceptance of Tubectomy - Devidas T Khedkar; Sushil Dalal; Jitendra S Bhawalkar; Jyoti A Landge (Medsci Publications, 2016)
Background: Very rapidly growing current population is one of the major social problems in India. Tubectomy is the most commonly used contraceptive since its introduction in the National Family Planning Programme. Some eligible women accept this method and others do not, this study is trying to probe that. Objective: The present study was conducted with an objective to study and compare the determinants of differential behaviour and some fertility factors in acceptors and non-acceptors of tubectomy. Materials and Methods: It's an observational, analytical, case control study; for which data is collected through direct interviews with study subjects by trained staff in structured and pretested proforma. The statistical variables used were means and 'p' Value of Chi square test obtained by subjecting data to 'epi-info' software. Results: The average number of total living children, sons and daughters per acceptor were found to be 2.29, 1.35 and 0.94 respectively and for non acceptors; they were 2.20, 0.85 and 1.35 respectively. Conclusions: Highly significant associations were observed between the number of sons and acceptance of tubectomy and the number of daughters and non-acceptance of tubectomy.